Prevalence and Genetic Relationship of Predominant Escherichia coli Serotypes Isolated from Poultry, Wild Animals, and Environment in the Mekong Delta, Vietnam - Lam Thanh Nguyen; Nguyen Khanh Thuan; Nguyen Thu Tam; Chau Thi Huyen Trang; Nguyen Phuc Khanh; Tran Ngoc Bich; Takahide Taniguchi; Hideki Hayashidani; Ly Thi Lien Khai (Veterinary Medicine International)
Avian pathogenic Escherichia coli (APEC) is the main causative agent of avian colibacillosis, which is an important systemic disease of profound economic and clinical consequences for the poultry industry worldwide. In this study, 975 E. coli strains were isolated from 2,169 samples collected from cloacal swabs of chickens, in-farm wild animals (ants, geckos, flies, and rats), and environment. The highest proportion of E. coli isolation was obtained from chicken cloacal swabs with 71.05% (95% confidence interval (CI) 66.69–75.05%) followed by the proportions of 38.15% (95% CI 35.41–40.97%) and 38.11% (95% CI 34.15–42.24%) from wild animals or environment, respectively. Distribution of O-antigen serotypes of the E. coli isolates, including O1, O2, O18, and O78, was determined by PCR. The most predominant serotype was O18 (10.56%) followed by O2 (9.44%), O1 (7.79%), and O78 (6.56%). Of note, serotype O18 was more likely distributed in the examined wild animals, especially in geckos. Polymorphic DNA fingerprints, generated by ERIC-PCR, of representative E. coli strains of each serotype revealed genetic heterogeneity of the examined E. coli, and O18 was more divergent with 63 clusters formed from 66 isolates. Furthermore, several E. coli strains from different sample sources shared high DNA fingerprint relatedness, suggesting that there exists complex transmission of E. coli from chickens to wild animals and environment and vice versa in poultry husbandry settings. Although pathotypes of the examined E. coli were not determined in this study, our results provided important findings of epidemiological and genetic characteristics of E. coli in the Mekong Delta and highlighted the prerequisite of stricter biocontainment to reduce the prevalence and consequences of APEC in poultry production.